BURDEN OF PROOF IN OVERTIME WAGE CLAIMS - Nadaek, Nason; Wijaya, Adi (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Overtime wage demands occur when the company employs workers overtime, but the workers are not given overtime wages, so the workers are forced to make a report or complaint to the labor inspector, to conduct an examination as a basis for calculating and determining, because overtime wages are a right guaranteed by labor legislation. According to Prof. Dr. H.R Abdussalam, SIK, SH, MH and Adri Desasfuryanto, SH, MH, working hours are 7 (seven) hours a day and 40 (forty) hours a week and in the event that workers work beyond these working hours, then workers are entitled to overtime pay Keywords: Prosecution, imposition, evidence.